Observation of chicJ radiative decays to light vector mesons. - Bennett, J; Mitchell, R; Shepherd, MR; Besson, D; Pedlar, T; Cronin-Hennessy, D; Gao, K; Hietala, J; Kubota, Y; Klein, T; Lang, B; Poling, R; et al. (2008)
Using a total of 2.74 x 10(7) decays of the psi(2S) collected with the CLEO-c detector, we present a study of chi(cJ)-->gammaV, where V=rho(0), omega, phi. The transitions chi(c1)-->gammarho(0 and chi(c1)-->gammaomega are observed with B(chi(c1)-->gammarho(0))=(2.43+/-0.19+/-0.22) x 10(-4) and B(chi(c1)-->gammaomega)=(8.3+/-1.5+/-1.2) x 10(-5). In the chi(c1)-->gammarho(0) transition, the final state meson is dominantly longitudinally polarized. Upper limits on the branching fractions of other chi(cJ) states to light vector mesons are presented.